General Considerations on the Impact of Transfer Pricing Performed by Multinational Companies on a National Economy - Rica Ivan; Calin Tanase Ladar (Agora International Journal of Economical Sciences (AIJES), 2017)
The presence of an increasing number of multinational companies leads to an increase in the number of international transactions due to trade between entities belonging to these companies, but also due to exchanges with other international companies. Transactions made by the entities belonging to the same multinational company are influenced by the laws in force which apply to a national economy and which regulates international money flows; such laws have different provisions from one country to another, and thus generating income losses for these companies. At the same time, revenue transfers made by multinational companies can cause revenue losses to the budgets of those host states where these revenues are generated, governments being very concerned about transfer pricing. Thus, it is worth noticing the main methods used by multinationals in terms of transfer pricing policy, what is the impact of these transfers on a national economy, especially on Romania's economy, and what measures governments take to counteract the loss of budget revenues due to transfer pricing.
Keywords: 330